MMR and Tetraviral vaccination coverage from 2013 to 2023 in the North region: A temporal trend analysis (Research, Society and Development, 2024)
This study aims to identify the temporal trend in MMR and tetraviral vaccination coverage (CV) in the Northern region of Brazil, from 2013 to 2023. Ecological study of time series, retrospective and quantitative, with data from the SI-PNI, analyzed with the aid of the Microsoft Excel, BioEstat and Stata programs, to test the CV relationship according to the states in the North region, during the studied period. The CVs of D1 and D2 of Triple and Tetraviral in the North region from 2013 to 2023 fluctuated, with 2014 being the year with the highest rates for all immunobiologicals considered. The year 2023 had the lowest CVs, and the lowest rate was in 2021 for Tetraviral. The state with the highest CV in the period was Rondônia (79%), while the lowest was Pará (54.97%). The variance of CVs between states was significant using the ANOVA test. The observed temporal trend was decreasing. Possible causes for this include vaccine shortages due to structural deficiencies in local health services and vaccine hesitancy, due to a lack of trust and perception of risks. Disparities between states are notable: Rondônia and Tocantins have the largest CVs, and Pará and Acre the smallest. The temporal analysis indicates a sharp drop in 2020, attributed to political changes and defunding. Venezuelan immigration has also contributed to disease outbreaks due to low CV. Finally, it is important to address historical negligence and the need for federal mobilization to address the immunization problem in the region.